Validation of the Pilipino test in the Universtiy High School entrance examinations - Jorda, Maxima N. 1934- (s.n.], 1966)
The author tested the validity of the revised Pilipino Test used in the University High School entrance examinations as a tool for admissions for the school year 1965-1966. The characteristics of the test and its test items in relation to a particular group study, and in consonance with the objectives for which the test has been primarily designed are presented. Findings of the study reveal that the Pilipino Test is a good testing device for admission.